Penyuluhan Hukum tentang Pengenalan Cyberbullying pada Siswa SDN 1 Menteng dan SDN 11 Palangka Kota Palangka Raya - Hayati, Mulida; Aristoteles, Aristoteles; Junisya, Angelica Rya (Universitas Pahlawan Tuanku Tambusai, 2025)
The phenomenon of cyberbullying poses a serious challenge in the digital era, significantly affecting children’s psychological and social development. This community service program was conducted at SDN 1 Menteng and SDN 11 Palangka, Palangka Raya, aiming to enhance the understanding of students, parents, and teachers regarding the dangers of cyberbullying and its preventive strategies. Using a participatory approach through education, discussions, and simulations, the program successfully strengthened collective awareness of the importance of digital literacy and shared supervision. The results indicate that families play a central role as primary supervisors, schools act as facilitators of character education and digital ethics, while the community supports by creating a safe ecosystem. With the synergy of these three elements, cyberbullying prevention can be implemented more effectively and sustainably.